Estimating the Effect of Hierarchies on Information Use - Liberti, Jose M.; Mian, Atif R. (Review of Financial Studies, 2009)
Theory suggests that greater hierarchical distance between a subordinate and his boss makes it more difficult to share abstract and subjective information in decision making. A novel dataset put together from credit dossiers of large corporate loan applicants enables us to observe the information collected by loan officers, and how it is used by the ultimate loan approving officer. We find that greater hierarchical/geographical distance between the information collecting agent and the loan approving officer leads to less reliance on subjective information and more on objective information. By exploiting nonlinearities in the “assignment rules” that determine an applicant's hierarchical distance, and using information collecting agent fixed effects, we show that our result cannot be driven by endogenous assignment of applicants. We also find that higher frequency of interactions between the information collecting agent and loan approving officer, both over time and through geographical proximity, helps mitigate the effects of hierarchical distance on information use. Our results show that hierarchical distance influences information use, and highlights the importance of “human touch” in communication.